Faktor yang Berhubungan dengan Kejadian Penyakit Jantung Koroner (PJK) pada Penduduk di Wilayah Perkotaan dan Perdesaan: Analisis Data Survei Kesehatan Indonesia (SKI) 2023 - Resti Evita Sari; Muhammad Syukri; Ashar Nuzulul Putra; Rd. Halim (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Differences in socioeconomic and lifestyle characteristics between urban and rural populations may shape the distribution of CHD risk factors, but comparative evidence remains limited. This study examined factors associated with CHD among adults aged ≥35 years between urban and rural areas. A cross-sectional study was conducted using data from the 2023 Indonesian Health Survey, including 426,581 respondents aged ≥35 years. Data were analyzed using univariate, bivariate, and multivariable logistic regression. CHD prevalence was higher in urban than rural areas (2.3% vs. 1.1%). In urban areas, CHD was significantly associated with older age (adjusted prevalence odds ratio [aPOR] for ≥75 years: 7.11; 95% CI: 5.30–9.55), hypertension (aPOR: 4.83; 95% CI: 4.27–5.47), diabetes mellitus (aPOR: 2.67; 95% CI: 2.26–3.17), low physical activity (aPOR: 1.48; 95% CI: 1.25–1.76), sex (aPOR: 1.21; 95% CI: 1.08–1.37), and alcohol consumption (aPOR: 0.53; 95% CI: 0.36–0.78). In rural areas, significant factors included older age (aPOR for ≥75 years: 2.68; 95% CI: 1.69–4.23), hypertension (aPOR: 5.66; 95% CI: 4.62–6.93), diabetes mellitus (aPOR: 3.57; 95% CI: 2.67–4.77), low physical activity (aPOR: 1.70; 95% CI: 1.22–2.37), smoking (aPOR: 0.55; 95% CI: 0.42–0.73), sex (aPOR: 1.38; 95% CI: 1.10–1.73), and low vegetable consumption (aPOR: 2.57; 95% CI: 1.20–5.49). Hypertension was the strongest factor associated with CHD in both urban and rural areas. Targeted prevention strategies should prioritize hypertension control and context-specific healthy lifestyle interventions.